Sustainable Development Prospects of the Mangrove Relic of Foulpointe – East Madagascar - Rakotomavo, Andriamparany; Mandimbinirina, Diary Salohy; Roger, Edmond (Emerging Issues in Environment, Geography and Earth Science Vol. 8, 2024)
The Malagasy East coast accounts for nearly 2% of Malagasy mangroves. Located about fifty kilometers North of Toamasina (East Madagascar), the Commune of Mahavelona Foulpointe has a mangrove relic of about 2 hectares. Despite the ecological and socio-economic roles played by this ecosystem, it remains so far an orphan site, both in terms of official management and development. The purpose of this article is to take stock of the situation with a view to proposing methods for the sustainable development of this small mangrove via valuation of its natural dynamics. Systematic floristic inventory work was carried out, following a linear ABC transect of 50-100 m, from the sea (zone C) to the rear mangrove (zone A). Factor Correspondence Analysis (FCA), combined with Principal Component Analysis (PCA) identified the plant groups and these methods were combined with the diachronic analysis of the 2009 and 2016 satellite images under the Geographical Information System. Five mangrove species exist at Foulpointe: Avicennia marina, Sonneratia alba, Bruguiera gymnorrhiza, Rhizophora mucronata, Lumnitzera racemosa. With anthropogenic harvesting and tourism activities in the areas, this ecosystem suffers an annual spatial loss of about 0.14 ha between 2009 and 2016. With a natural regeneration rate of about 966 % the small mangrove has a strong capacity for regeneration. Taking into account the pace of current clearing, it would disappear in 10-15 years. The valorization of regenerated young plants, followed by intensive preservation and restoration actions, constitutes a sustainable development path. The stakeholders play an important role in the sustainable management of the Foulpointe mangrove relic. The knowledge of the Foulpointe mangrove forest, which until now, remains little known in terms of structures and pressures, two basic information essential for its sustainable development and management. The renaturation of the site through a natural approach favoring regenerations and the natural reconstitution process.